IMPLEMENTASI PROGRAM BANTUAN OPERASIONAL SEKOLAH PADA SEKSI PEMBINAAN SEKOLAH MENENGAH PERTAMA DINAS PENDIDIKAN DAN KEBUDAYAAN DAERAH PROPINSI SULAWESI TENGAH - Rinmawan, Rinmawan (Katalogis, 2015)
This study aims at determining how the implementation of School Operational Assistance Program (BOS) at the Development Division of Junior High School in the Department of Education and Culture, Central Sulawesi. This research used descriptive qualitative method and the data collection techniques were through observations, interviews, and documentations. This research used purposive sampling technique and five informants were taken. The results show that the program implementation has run well. The results also show that the program implementation were affected by some aspects according to George Edward III implementation approach, they were: 1) Aspect of communication: the implementation of School Operational Assistance Program (BOS) at the Development Division of Junior High School in the Department of Education and Culture, Central Sulawesi has been good, 2) Aspect of resources has been good. 3) Aspect Disposition has been good. 4) Aspect of Bureaucratic Structure is good.